Do all cardiac surgery patients benefit from antifibrinolytic therapy?. Issue 4 (14th February 2021) - Sussman, Matthew S.; Urrechaga, Eva M.; Cioci, Alessia C.; Iyengar, Rahul S.; Herrington, Tyler J.; Ryon, Emily L.; Namias, Nicholas; Galbut, David L.; Salerno, Tomas A.; Proctor, Kenneth G.
Abstract: Background: In trauma patients, the recognition of fibrinolysis phenotypes has led to a re‐evaluation of the risks and benefits of antifibrinolytic therapy (AF). Many cardiac patients also receive AF, but the distribution of fibrinolytic phenotypes in that population is unknown. The purpose of this hypothesis‐generating study was to fill that gap. Methods: Seventy‐eight cardiac surgery patients were retrospectively reviewed. Phenotypes were defined as hypofibrinolytic (LY30 <0.8%), physiologic (0.8%–3.0%), and hyperfibrinolytic (>3%) based on thromboelastogram. Results: The population was 65 ± 10‐years old, 74% male, average body mass index of 29 ± 5 kg/m 2 . Fibrinolytic phenotypes were distributed as physiologic = 45% (35 of 78), hypo = 32% (25 of 78), and hyper = 23% (18 of 78). There was no obvious effect of age, gender, race, or ethnicity on this distribution; 47% received AF. For AF versus no AF, the time with chest tube was longer (4 [1] vs. 3 [1] days, p  = .037), and all‐cause morbidity was more prevalent (51% vs. 25%, p  = .017). However, when these two groups were further stratified by phenotypes, there were within‐group differences in the percentage of patients with congestive heart failure ( p  = .022), valve disease ( p  = .024), on‐pump surgery ( p  < .0001), estimated blood loss during surgery ( p  = .015), transfusion requirement ( p  = .015), and chest tube output ( p  = .008), which highlight other factors along with AF that might have affected all‐cause morbidity. Conclusion: This is the first description of the prevalence of three different fibrinolytic phenotypes and their potential influence on cardiac surgery patients. The use of AF was associated with increased morbidity, but because of the small sample size and treatment allocation bias, additional confirmatory studies are necessary. We hope these present findings open the dialog on whether it is safe to administer AFs to cardiac surgery patients who are normo‐ or hypofibrinolytic.